Case report: Germline RECQL mutation potentially involved in hereditary predisposition to acute leukemia - Yuan, Wei; Shang, Zhen; Shen, Kefeng; Yu, Qiuxia; Lv, Qiuxia; Cao, Yang; Wang, Jue; Yang, Yi (Frontiers in Oncology, 2023)
The pathogenesis of acute leukemia is still complex and vague. Most types of acute leukemia are related to somatic gene mutations, and familial incidence is rare. Here we report a case of familial leukemia. The proband presented to our hospital with vaginal bleeding and disseminated intravascular coagulation at the age of 42 and was diagnosed with acute promyelocytic leukemia with typical PML-RARα fusion gene caused by t(15;17)(q24;q21) translocation. By taking the history, we found that the patient's second daughter had been diagnosed with B-cell acute leukemia with ETV6-RUNX1 fusion gene at age 6. Then we performed whole exome sequencing in peripheral blood mononuclear cells from these two patients at remission status and identified 8 shared germline gene mutations. Using functional annotation and Sanger sequencing validation, we finally focused on a single nucleotide variant in RecQ like helicase (RECQL), rs146924988, which was negative in the proband's healthy eldest daughter. This gene variant potentially led to a relative lack of RECQL protein, disordered DNA repair and chromatin rearrangement, which may mediate the occurrence of fusion genes, as driving factors for leukemia. This study identified a novel possible leukemia-related germline gene variant and provided a new understanding for the screening and pathogenesis of hereditary predisposition syndromes.